Mhc Class II DNA Polymorphisms within and between Chromosomal Species of the Spalax Ehrenbergi Superspecies in Israel - Ben-Shlomo, R. (1988)
Restriction fragment length polymorphisms (RFLPs) of two major histocompatibility class II genes (Pα(1) and Qβ) were studied in 13 populations of four chromosomal species (2n = 52, 54, 58 and 60) of the mole rat, Spalax ehrenbergi superspecies in Israel. A substantial frequency of allelic fragments was found in both genes for all populations, including a desert isolate. In the Pα(1) gene, one allelic fragment is a result of a deletion mutation which is diagnostic of the 2n = 52 chromosomal species. All other ten allelic variants are the result of point mutations. All mutations are located in a short region flanking the 3' end of the gene. Based on Mhc polymorphisms we confirm earlier evidence that gene flow does not occur between the older chromosomal species (2n = 52, 54, 58), and that reproductive isolation decreases, progressively from the oldest to the youngest species (2n = 60).